Gender differences learning strategy at English Language Education Department Students University Of Muhammadiyah Malang - Thathit Manon Andini; Santi Prastiyowati (University of Muhammadiyah Malang, 2021)
Gender difference can be assumed as an individual difference generally existing and catching attention in the foreign language teaching and learning.This research aims at finding out the strategies used by the students in learning English and students’ perspective on the learning strategies based on their gender. The data are gathered through questionnaires and interview which are given to the students of English Language Education Department. This study discovered that male and female students differ in the learning strategy, and the female students score higher in the use of learning strategy than the males. Metacognitive and social learning strategy were highly used by female students. On the other hand, male students score compensation, metacognitive and cognitive learning strategy as their attempts to learn English. The result also found that females use all the strategies more often than males particularly on metacognitive strategy. Moreover, there are differences in the use of other strategies, but the finding is not remarkable.